EFFECTS OF SHOT PEENING ON HARDNESS OF 18CRNIMO7-6 STEEL BASED ON FINITE ELEMENT ANALYSIS - CHEN HaiKuan; XU GuangTao; SUN Bo; WANG BingBing (Jixie qiangdu)
So far, most of the numerical studies on shot peening are limited in the effects of shot peening parameters on the residual stress and surface morphology. There is still lack of numerical research on shot peening parameters on the hardness. Against this issue, studies are carried out for shot peening parameters on the hardness of 18 CrNiMo7-6 alloy steel based on a random multi-shot finite element model and empirical relationship between yield strength and Vickers hardness. Numerical results show that the surface hardness increases with coverage rates, and the thickness of hardness layer increases with the radius and velocity of shots.